PERTUMBUHAN DAN SERANGAN HAMA PADA TANAMAN JABON (Antocephalus cadamba) UMUR EMPAT TAHUN - Prijono, Agus (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2016)
Wood consumption in Indonesia is increasing, meanwhile wood from natural forest is decreasing. Consequently the wood industry is widely supplied from fast growing plantation forests, with 15 years rotation or 10 m3 /ha/year growth yield. One of fast growing species is Jabon (Antocephalus cadamba) which can be harvested at 5 years with the price of Rp 900,000.00 per cubic meter. Jabon has been planted in various areas, one of them in Widodomartani, Ngemplak, Sleman, Yogyakarta Province. Jabon is a new plant in the Widodomartani community and has not been widely known for its growth. This research aims to determine the growth and pest attacks on plants jabon. The growth data (height and diameter) was taken from the sample in each treatment (6 treatments). The number of samples in each treatment was 10 trees repeated 3 times, so the total sample was 30 trees for each treatment. The data obtained were analyzed by ANOVA and if there were significant differences in the factors, followed by the LSD test. The growth rate of jabon at 4 years planted on 2 x 2 meters spacing is moderate, with live percentage of 73.31%, plant height 13.59 m and 10.71 cm diameter. Types of pests that attack jabon include stem borer with low attack intensity (8.6%) but cause severe damage (dead plants 83.33%), and leaf caterpillar with a total attack intensity (100%) but resulted in moderate damage levels (60.52% of live plants). Keywords : Growth, Pest Attack, Antocephalus cadamba